STUDENT'S LEARNING DIFFICULTIES ON MATHEMATICAL UNDERSTANDING OF A NUMBER PATTERN - Ratu Sarah Fauziah Iskandar; Darhim Darhim; Jarnawi Afgani Dahlan; Al Jupri (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Number patterns are a fundamental aspect of mathematics, often serving as a bridge between arithmetic and algebra. Number patterns often require students to think abstractly, identifying relationships and rules that govern the sequence of numbers. For some people, this transition from concrete to abstract thinking can be difficult. Encouraging students to visualize patterns using concrete objects or images can help bridge this gap, making abstract concepts more real. The aim of this study was to investigate the students' difficulties and how grade 9 students' mathematics approaches to number pattern problems. 32 students from a junior high schools in Tangerang participated in this case study. Purposive sampling technique is used in this study. The stages of the preliminary study involve interviewing the mathematics teacher regarding learning, administering preliminary exams, and evaluating the outcomes of the preliminary exams. Research data was collected through tests and interviews. These interviews took place post the analysis of initial test (a diagnostic tests). The result showed that the difficulty in discerning the regularity of the numerical arrangement: 1) In calculating the formula for the nth term in a number pattern, modeling is used; 2) Students frequently employ the direct proportion method to generalize patterns without taking into account the overall arrangement of numbers; 3) Observing the arrangement of numbers causes uncertainty in seeing order; 4) In generalizing number patterns, damage occurs; 5) illustrating that number patterns always have regularities, and these regularities are not always in the form of numerical differences.Pola bilangan adalah aspek mendasar dari ilmu matematika dan sering kali dianggap sebagai jembatan antara aritmatika dan aljabar. Pola bilangan mengharuskan siswa untuk berpikir abstrak, mengidentifikasi hubungan dan aturan yang mengatur barisan bilangan. Bagi sebagian orang, transisi dari pemikiran konkrit ke abstrak bisa jadi sulit. Mendorong siswa untuk memvisualisasikan pola menggunakan objek atau gambar konkret dapat membantu menjembatani kesenjangan ini, menjadikan konsep abstrak menjadi lebih nyata. Tujuan dari penelitian ini adalah untuk menyelidiki kesulitan siswa terhadap masalah pola bilangan pada siswa kelas 9. Adapun subjek dalam penelitian studi kasus ini adalah 32 orang siswa SMP di Tangerang. Teknik pengambilan sampel adalah dengan menggunakan teknik purposive sampling. Tahapan studi pendahuluan meliputi wawancara kepada guru matematika mengenai pembelajaran, pelaksanaan tes awal, dan evaluasi hasil ujian. Data penelitian dikumpulkan melalui tes dan wawancara. Wawancara ini dilakukan pasca analisis tes awal (tes diagnostik). Hasil penelitian menunjukkan bahwa kesulitan dalam membedakan keteraturan susunan bilangan: 1) Menggunakan pemodelan dalam menghitung rumus suku ke-n suatu pola bilangan; 2) Siswa sering menggunakan metode perbandingan langsung untuk menggeneralisasi pola tanpa memperhitungkan susunan bilangan secara keseluruhan; 3) Mengamati susunan bilangan menimbulkan ketidakpastian dalam melihat keteraturan; 4) Dalam menggeneralisasi pola bilangan, terjadi ketidaksesuaian; 5) menggambarkan bahwa pola bilangan selalu mempunyai keteraturan, dan keteraturan tersebut tidak selalu berupa perbedaan angka.